Development of Industrial Cooperation within the EAEU - DOLGOV, Sergey Ivanovich; SAVINOV, Yuri Anatolyevich; TARANOVSKAYA, Evgeniya Vadimovna; SEKERIN, Vladimir Dmitrievich; GOROKHOVA, Anna Evgenyevna (Journal of Advanced Research in Law and Economics; Vol 10 No 2 (2019): JARLE Vol X Issue 2(40) Spring 2019DO - 10.14505//jarle.v10.2(40).12, 2020)
The research considers the phased development of industrial cooperation among the member countries of the Eurasian Economic Union. The authors analyze the main regulatory documents and trends in the expansion of cooperation among the Union's industrial enterprises. Particular attention is paid to cooperation in the industry. The authors have calculated the Spearman’s rank correlation coefficient, which reflects the rank coincidence rate of the commodity items in mutual trade. The calculations have allowed to reveal that an increase in the rank coincidence rate of commodity items in the mutual exports indicated the predominant development of mutual trade in goods of one commodity group, i.e. the deepening of intra-industry cooperation and the stimulating effect of this cooperation on the growth of mutual trade.